A novel antigen capture ELISA for the specific detection of IgG antibodies to elephant endotheliotropic herpes virus. Issue 1 (December 2015) - van den Doel, Petra; Prieto, Víctor; van Rossum-Fikkert, Sarah; Schaftenaar, Willem; Latimer, Erin; Howard, Lauren; Chapman, Sarah; Masters, Nic; Osterhaus, Albert; Ling, Paul; Dastjerdi, Akbar; Martina, Byron
Abstract Background Elephants are classified as critically endangered animals by the International Union for Conservation of Species (IUCN). Elephant endotheliotropic herpesvirus (EEHV) poses a large threat to breeding programs of captive Asian elephants by causing fatal haemorrhagic disease. EEHV infection is detected by PCR in samples from both clinically ill and asymptomatic elephants with an active infection, whereas latent carriers can be distinguished exclusively via serological assays. To date, identification of latent carriers has been challenging, since there are no serological assays capable of detecting seropositive elephants. Results Here we describe a novel ELISA that specifically detects EEHV antibodies circulating in Asian elephant plasma/serum. Approximately 80 % of PCR positive elephants display EEHV-specific antibodies. Monitoring three Asian elephant herds from European zoos revealed that the serostatus of elephants within a herd varied from non-detectable to high titers. The antibody titers showed typical herpes-like rise-and-fall patterns in time which occur in all seropositive animals in the herd more or less simultaneously. Conclusions This study shows that the developed ELISA is suitable to detect antibodies specific to EEHV. It allows study of EEHV seroprevalence in Asian elephants. Results confirm that EEHV prevalence among Asian elephants (whether captive-born or wild-caught) is high.